ANALISIS NILAI MORAL PADA CERITA RAKYAT MALIN KUNDANG, TIMUN MAS, DAN DANAU TOBA DALAM BUKU BAHASA INDONESIA KELAS 3 SEKOLAH DASAR - Novayana Novayana; Lailatul Qodri Khairum Alfi (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Folk tales are one of Indonesia's cultural heritages that are rich in moral values and life lessons. The aim of this research is to analyze the moral values of three popular folk tales commonly taught in elementary schools: Malin Kundang, Timun Mas, and Danau Toba. This research uses a literature review method. The analysis results show that these folk tales contain various moral values such as responsibility, honesty, simplicity, courage, and gratitude. Additionally, there are social values such as respecting parents, loving family, maintaining trust, and avoiding arrogance. Therefore, folk tales serve as an important means of personal development that can strengthen social and cultural relationships within society.